Transition from monetary to inflation targeting in Nigeria : a background paper - Central Bank of Nigeria; Dogo, Mela Y. (Abuja, Nigeria Central Bank of Nigeria, 2016)
The study identifies monetary policy instruments and inflation measures most suited for transiting from monetary to inflation targeting monetary policy framework in Nigeria using quarterly data for 1981Q1 to 2013Q3.
Includes bibliographical references
oif 06/02/2020
Loans
Keywords: Inflation; Nigeria